The challenges of e-commerce application among SMEs in West Coast of Sabah: A preliminary study - Ismail, Hadzariah; Salimun, Carolyn; Obit, Joe Henry (2005)
This article investigates the challenges related to social, technological, and investment issues of e-commerce application among small-medium-sized enterprises (SMEs) in west coast of Sabah. The result of these study stressed that the application of e-commerce are very important and need to be implemented widely especially in Sabah to make it more competitive and creative in order to compete in global market.